2018
DOI: 10.1080/14697688.2018.1508879
|View full text |Cite
|
Sign up to set email alerts
|

Gold price dynamics and the role of uncertainty

Abstract: This study adopts a copula wavelet approach to analyze dynamics of the gold price against bonds, stocks and exchange rates based on disaggregation of the underlying relationships across different frequencies. We also examine whether gold prices are directly affected by changes in uncertainty. Analyzing data for nine economies for a sample period starting in 1985, we find that the role of gold changes significantly after the collapse of Lehman Brothers in 2008. Gold is unable to serve as a hedge in the classica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 32 publications
6
45
1
Order By: Relevance
“…Interestingly, as documented by the previous studies on the same issue, we show that the different uncertainty measures display heterogenuous impacts on gold returns (for example, Blose, 2010; Jones and Sackley, 2016;Balcilar et al 2016;Beckmann et al 2017). Fig 2 (a) reports the estimate of the gold return's reaction to the macroeconomic uncertainty.…”
Section: 1the Quantile-on Quantile Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Interestingly, as documented by the previous studies on the same issue, we show that the different uncertainty measures display heterogenuous impacts on gold returns (for example, Blose, 2010; Jones and Sackley, 2016;Balcilar et al 2016;Beckmann et al 2017). Fig 2 (a) reports the estimate of the gold return's reaction to the macroeconomic uncertainty.…”
Section: 1the Quantile-on Quantile Resultssupporting
confidence: 76%
“…Previous empirical studies documented that the linkage between gold and other assets changes noticeably in times of market stress or turmoil (Hartmann et al 2004;Baur and McDermott, 2010;Baur and Lucey, 2010;Wang et al, 2011;Miyazaki et al, 2012;Ciner et al 2013;Mensi et al, 2013;Reboredo, 2013;Wang and Chueh, 2013;Arouri et al, 2015;Bampinas and Panagiotidi, 2015;Beckmann et al, 2015;Nguyen et al, 2016;Van Hoang et al, 2016, among others). Although the empirical literature on the dependence between gold prices and other assets is increasing remarkably, Beckmann et al (2017) suggested that the traditional and the well-known view on hedge and safe haven properties of gold can be misleading and that it seems more relevant to directly assess the dependence between gold and uncertainty.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The positive gold shocks may increase the probability of being in the high-uncertainty regime (Zhou et al, 2017). In general, there is a mutual influence between GEPU and GP (Balcilar et al, 2016;Raza et al, 2018;Beckmann et al, 2019). According to this mutual influence, it assists the governments to forecast and stabilize the global economy, based on the price of gold, and it also inspires the investors to hedge risks of GEPU, by rationally arranging assets.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction There exists a large literature that has looked into the "safe haven" status of gold relative to stock, bond and currency markets (see for example, Baur and Lucey (2010), Baur and McDermott (2010), Reboredo (2013a), Agyei-Ampomah et al, (2014), Gürgün and Ünalmis (2014), Beckmann et al, (2015)), as well as oil prices (Reboredo, 2013b;Tiwari et al, 2019). More recently, studies have also analyzed the role of economic uncertainty and geopolitical risks, i.e., non-financial indicators, as drivers of gold prices in the context of its safe haven property (see for example, Baur and Smales (2018), Bouoiyour et al, (2018), Beckmann et al, (2019)).…”
mentioning
confidence: 99%